If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -2 = 2(x + -6) Reorder the terms: -2 + 4x = 2(x + -6) Reorder the terms: -2 + 4x = 2(-6 + x) -2 + 4x = (-6 * 2 + x * 2) -2 + 4x = (-12 + 2x) Solving -2 + 4x = -12 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -2 + 4x + -2x = -12 + 2x + -2x Combine like terms: 4x + -2x = 2x -2 + 2x = -12 + 2x + -2x Combine like terms: 2x + -2x = 0 -2 + 2x = -12 + 0 -2 + 2x = -12 Add '2' to each side of the equation. -2 + 2 + 2x = -12 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = -12 + 2 2x = -12 + 2 Combine like terms: -12 + 2 = -10 2x = -10 Divide each side by '2'. x = -5 Simplifying x = -5
| 3(2x+5)=ax+5 | | 4(5x+2)-6x=5(2x+4) | | 60X=0.1 | | 6(8+x)=78 | | 4x-6x=2x | | 9(2n-5)=(9n+7)+8 | | 61x^2+56x+4=0 | | -2x+4=4x+16 | | (x-15)(x+3)=0 | | 7(12+y)=4 | | 3t+10=16 | | 3/5n-10=2/5n | | -42=4v-8 | | 5/x-3/5=20 | | 6x+5+7x=34 | | -11b+5+9b=-3b+10 | | 6X+48Y+8Z=2400 | | 20=(150+20p)-(10+30p) | | 61-6x=-11 | | 3y-2=3(2+y) | | (4-3i)(5+i)=0 | | 2n-3(4n+5)=-6+17 | | 2(x-7)=15 | | 4x-2[2-3(3-5x)]=1 | | 4x-2[2-3(3-4x)]=1 | | 2(3x-7)+4=10 | | -7y+3+8y=12-20 | | 2(6x-5)(4x+5)=0 | | -5-5=0 | | 3+log^4(2x+6)=6 | | -16=-2(3+x) | | (-4i)(6i)=0 |